Human liver flukes. (September 2017) - Harrington, David; Lamberton, Poppy H L; McGregor, Alastair
Summary: Liver fluke infections occur in people worldwide. In some low-income regions, a combination of ecological, agricultural, and culinary factors leads to a very high prevalence of infection but, in higher-income regions, infections are uncommon. Infection is associated with substantial morbidity and several liver fluke species are recognised as biological carcinogens. Here, we review the epidemiology, clinical significance, and diagnostic and treatment strategies of human infection with these pathogens.